PERKEMBANGAN SOSIAL EMOSIONAL PADA ANAK USIA TAMAN KANAK-KANAK DI TK AL ISLAM - Jon Iskandar Bahari (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Human life is very rich in emotional experiences. It's just that there are very strong impulses, some are very faint so that his expression was not visible. Emotional expressions we will recognize at every age level from babies to adults, both boys or women. For example, a child laughs with joy when his father bounces his body in the air or we see a child a one year old crying because his toy was taken by her brother. For a child, this emotional state is easier to express through his physical condition. For example a child will go straight cry when he feels sick or uncomfortable. However, if a child is asked “how he feels” or “why he is feel sick? ”, the child will find it difficult to express his feelings in verbal language. According to Plato, potentially (fitrah) humans are born as social creatures (zoon politicon). Syamsuddin reveals that